Adenovirus vector-based vaccine for infectious diseases. (February 2022) - Sakurai, Fuminori; Tachibana, Masashi; Mizuguchi, Hiroyuki
Abstract: Replication-incompetent adenovirus (Ad) vectors have been widely used as gene delivery vehicles in both gene therapy studies and basic studies for gene function analysis due to their highly advantageous properties, which include high transduction efficiencies, relatively large capacities for transgenes, and high titer production. In addition, Ad vectors induce moderate levels of innate immunity and have relatively high thermostability, making them very attractive as potential vaccine vectors. Accordingly, it is anticipated that Ad vectors will be used in vaccines for the prevention of infectious diseases, including Ebola virus disease and acquired immune deficiency syndrome (AIDS). Much attention is currently focused on the potential use of an Ad vector vaccine for coronavirus disease 2019 (COVID-19). In this review, we describe the basic properties of an Ad vector, Ad vector-induced innate immunity and immune responses to Ad vector-produced transgene products. Development of novel Ad vectors which can overcome the drawbacks of conventional Ad vector vaccines and clinical application of Ad vector vaccines to several infectious diseases are also discussed.